2021
DOI: 10.1186/s12889-021-11560-8
|View full text |Cite
|
Sign up to set email alerts
|

“Burnt by the scorching sun”: climate-induced livelihood transformations, reproductive health, and fertility trajectories in drought-affected communities of Zambia

Abstract: Background Climate-induced disruptions like drought can destabilize household and community livelihoods, particularly in low- and middle-income countries. This qualitative study explores the impact of severe and prolonged droughts on gendered livelihood transitions, women’s social and financial wellbeing, and sexual and reproductive health (SRH) outcomes in two Zambian provinces. Methods In September 2020, in-depth interviews (n = 20) and focus gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(43 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…Grace et al (2015) examined the relationship between birth weight, precipitation, and temperature in 19 African countries and showed that climate affects birth weight in ways that were correlated with the dependence on the dominant food production strategy. Rosen et al (2021) have demonstrated direct economic consequences of drought on women; from diminishing household assets to food insecurity, to increased risk of poor sexual and reproductive health outcomes.…”
Section: Impact On Healthmentioning
confidence: 99%
“…Grace et al (2015) examined the relationship between birth weight, precipitation, and temperature in 19 African countries and showed that climate affects birth weight in ways that were correlated with the dependence on the dominant food production strategy. Rosen et al (2021) have demonstrated direct economic consequences of drought on women; from diminishing household assets to food insecurity, to increased risk of poor sexual and reproductive health outcomes.…”
Section: Impact On Healthmentioning
confidence: 99%
“…While none of the included documents explicitly addressed the SRH needs of men, access to family planning, contraception, and STI prevention are pertinent to men both within and outside of marriage, and men and boys are important to include in SRH interventions, programming and solutions ( 38 , 39 ). Furthermore given climate-induced migration often involves the movement of men seeking employment, it is important to consider how this impacts them as well as their families' altered household structure ( 40 ). Achieving full and equitable SRH for the entire population, including in climate migration contexts, is not possible without engaging all genders and addressing gender inequality in societal and political structures ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Uncertainty has been linked with family planning preferences among Mayan women in Mexico (Kramer et al 2021) and another study in the United States reported an increase in contraceptive use as a result of the Great Recession of 2008 . Indeed, evidence from a qualitative study of women experiencing drought in Zambia showed that women expressed preferences for smaller families, fearing the drought would constrain their ability to support more children (Rosen et al 2021). Moreover, Thiede et al (2022) show that exposure to high temperatures and drought corresponds with a reduction in fertility-at least in the short term.…”
Section: Drought Fertility Preferences and Contraceptive Behaviors: C...mentioning
confidence: 99%
“…That is, being exposed to drought could lead women to want to accelerate childbearing to protect against what may be perceived as a persistent threat to their family that will only worsen with time. The disruption and uncertainty that drought generates in people's lives could, paradoxically, facilitate women's desire to have a(nother) child sooner than later (Bielawska-Batorowicz, Zagaj, and Kossakowska 2022;Dessy et al 2019;Rosen et al 2021).…”
Section: Drought Fertility Preferences and Contraceptive Behaviors: C...mentioning
confidence: 99%